2009
DOI: 10.1029/2008jd011281
|View full text |Cite
|
Sign up to set email alerts
|

Diurnally driven scaling properties of Amazonian rainfall fields: Fourier spectra and order‐q statistical moments

Abstract: [1] The influence of the diurnal cycle on spatial scaling properties of Amazonian rainfall fields is investigated using data gathered during the January-February 1999 Wet Season Atmospheric Meso-scale Campaign in the state of Rondonia (Brazil, SW Amazonia). Most intense precipitation events with large spatial coverage occur during early afternoon. Amplitudes of average and maximum intensity diurnal cycles are higher during the easterly than during the westerly atmospheric regime. The diurnal cycle of average r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…According to data from the NCEP-NCAR Reanalysis, as well as from the Fazenda Nossa Senhora radiosonde, the Easterly (negative values) and Westerly (positive) regimes are clearly differentiated in both data sets [19,31]. Furthermore, radar observations from southwestern Amazonia during TRMM-LBA suggest that there was relatively little difference in the daily mean rainfall totals between Easterly and Westerly regimes [57].…”
Section: Easterly and Westerly Regimes Of Amazonian Rainfallmentioning
confidence: 99%
See 4 more Smart Citations
“…According to data from the NCEP-NCAR Reanalysis, as well as from the Fazenda Nossa Senhora radiosonde, the Easterly (negative values) and Westerly (positive) regimes are clearly differentiated in both data sets [19,31]. Furthermore, radar observations from southwestern Amazonia during TRMM-LBA suggest that there was relatively little difference in the daily mean rainfall totals between Easterly and Westerly regimes [57].…”
Section: Easterly and Westerly Regimes Of Amazonian Rainfallmentioning
confidence: 99%
“…In particular, Ref. [19] found that 2-D rainfall fields over Amazonia exhibit multiscaling properties in space, which means that the relationship M r (λ) ∼ λ −τ(r) exhibits a non-linear behavior, where λ is the spatial scale, r the order of the statistical moment and τ(r) is the r-th moment scaling exponent. Additionally, they show that both the diurnal cycle and the predominant atmospheric regime of Amazonian rainfall (Easterly or Westerly) exert a strong control on the scaling properties of Amazonian storms, thus shedding light towards understanding the linkages between scaling statistics and physical features of Amazonian rainfall fields.…”
Section: Statistical Scaling and Multiplicative Random Cascadesmentioning
confidence: 99%
See 3 more Smart Citations